2015
DOI: 10.1111/sms.12506
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C and E supplementation blunts increases in total lean body mass in elderly men after strength training

Abstract: The aim of this study was to investigate the effects of vitamin C and E supplementation on changes in muscle mass (lean mass and muscle thickness) and strength during 12 weeks of strength training in elderly men. Thirty-four elderly males (60-81 years) were randomized to either an antioxidant group (500 mg of vitamin C and 117.5 mg vitamin E before and after training) or a placebo group following the same strength training program (three sessions per week). Body composition was assessed with dual-energy X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(70 citation statements)
references
References 40 publications
2
62
0
1
Order By: Relevance
“…In this study, rapamycin treatment (a pharmacological inhibitor of mTOR) completely abolished the hypertrophy effect, thus proving that mTOR is necessary for hypertrophy. It is interesting to note that, contrary to this study (where muscle antioxidant defense was decreased and muscle hypertrophy was optimized), other studies evaluating the impact of antioxidants in humans (through vitamin E and C supplementation) were shown to impair muscle hypertrophy response and cell signaling leading to muscle hypertrophy[45,46]. Several studies have observed that RT increases hypoxia, metabolite accumulation and ROS production, which seems to be strictly related[22,23,51,52].…”
Section: Resistance Trainingmentioning
confidence: 64%
See 1 more Smart Citation
“…In this study, rapamycin treatment (a pharmacological inhibitor of mTOR) completely abolished the hypertrophy effect, thus proving that mTOR is necessary for hypertrophy. It is interesting to note that, contrary to this study (where muscle antioxidant defense was decreased and muscle hypertrophy was optimized), other studies evaluating the impact of antioxidants in humans (through vitamin E and C supplementation) were shown to impair muscle hypertrophy response and cell signaling leading to muscle hypertrophy[45,46]. Several studies have observed that RT increases hypoxia, metabolite accumulation and ROS production, which seems to be strictly related[22,23,51,52].…”
Section: Resistance Trainingmentioning
confidence: 64%
“…In addition, studies have shown that utilization of antioxidants can modify protein signaling after a RT session and impairs muscle mass gains[45,46]. Muscle contractions during exercise produces ROS at low physiological levels and plays an important role in cell signaling to promote beneficial adaptations[47].…”
Section: Resistance Trainingmentioning
confidence: 99%
“… b ), while in older participants vitamin C has been report to attenuate gains in lean mass seen during 12 weeks (Bjornsen et al . ), but not 6 months, of resistance training (Bobeuf et al . ).…”
Section: Reactive Oxygen Species and Exercise Trainingmentioning
confidence: 99%
“…Many athletes use antioxidant supplements [11] in the belief they could further protect against exercise induced stress and thus improve recovery. However, recent studies indicate that antioxidant supplementation have the ability to blunt training adaptations in skeletal muscle [12,13]. A proposed mechanism for the observed interference between antioxidant supplementation and training adaptations has been related to changes in redox status in the muscle, which in turn might affect cell signaling [14].…”
Section: Introductionmentioning
confidence: 99%